2012
DOI: 10.1016/j.febslet.2012.11.026
|View full text |Cite
|
Sign up to set email alerts
|

PDT‐induced HSP70 externalization up‐regulates NO production via TLR2 signal pathway in macrophages

Abstract: a b s t r a c tWe studied the molecular mechanism underlying PDT-induced apoptosis-dependent macrophage activation, particularly through NO production. We demonstrate that NO production is initially induced by HSP70 on the apoptotic cell surface, and is further enhanced by macrophage phagocytosis. Additionally, we found that apoptotic cells, through TLR2, could activate PI3K, and this could be either dependent or independent of the activation of MyD88. These results reveal a novel pathway linking innate immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…In this study we demonstrated a positive correlation between the concentrations of Hsp70 and NO in the tissues examined, especially in benign tumours and grade I and grade II malignant tumours, which may indicate an interdependence of Hsp70 and nitrite ion production in canine mammary gland tumours. This is consistent with the findings of a recent study by Song et al (2013) who showed that apoptotic cells overexpressing Hsp70 induced a marked NO production in macrophages. This suggests that Hsp70 plays an important role both in the up-regulation of NO production and in the host's anti-tumour immunity.…”
Section: Discussionsupporting
confidence: 93%
“…In this study we demonstrated a positive correlation between the concentrations of Hsp70 and NO in the tissues examined, especially in benign tumours and grade I and grade II malignant tumours, which may indicate an interdependence of Hsp70 and nitrite ion production in canine mammary gland tumours. This is consistent with the findings of a recent study by Song et al (2013) who showed that apoptotic cells overexpressing Hsp70 induced a marked NO production in macrophages. This suggests that Hsp70 plays an important role both in the up-regulation of NO production and in the host's anti-tumour immunity.…”
Section: Discussionsupporting
confidence: 93%
“…The enhancement in angiogenic markers (NO, VEGF-A) observed in diabetic mice in response to PDT (Figs. 1a and 2a), could occur due to increase iNOS [28][29][30], release of protein-bound NO [31], and activation of hypoxia inducible factor VEGF signaling pathway [27]. However, these responses were reversed at the high APDT fluence, possibly due to the higher oxidative stress-induced damage to inflammatory cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…39 The role of ecto-HSP70 in ICD has not been strongly elucidated; however, at least in the case of PDT 11,22 ecto-HSP70 might favour nitric oxide (NO) production from innate immune cells. 7,22,40 In terms of capacity to mediate phagocytosis of dying cells by acting as an 'eat me' signal; an in silico analysis revealed that CRT harbours close homologues of crucial phagocytosis-assisting motifs, whereas HSP70/90 did not. 22 In agreement, the presence of ecto-CRT correlates better with increased phagocytosis of dying cancer cells than either ecto-HSP70/90.…”
Section: Viral Response and Icd: A New Connection?mentioning
confidence: 99%